Work Family Conflict dan Pengaruhnya terhadap Psychological Well Being pada Pekerja Pabrik Perempuan - Fridayanti Fridayanti; Yun Yun Yulinar (Universitas Muhammadiyah Jember, 2021)
Women who are married at the same time choose to work will easily be led to work family conflicts in which women will be faced with the demands of their respective roles. The purpose of this study was to determine whether family work conflated had an effect on psychological well being of female employees working in factories. This research is included in a quantitative study conducted on 108 female employees with an age range of 25-55 years and have a minimum service period of 1-2 years. Data was collected through filling out a questionnaire by modifying the work family conflict scale instrument from Khairuni Atikah (2018) based on Greenhaus Beutell's theory (1985) and the psychological well being scale from Mamluatul Khoiroh (2015) based on Ryff's theory (1989). Data analysis in this study used a simple regression analysis using the SPSS (Statistical Program for Social Science) version 24.0. The results of the research that has been done show that work family conflict has a negative effect on psychological well being where Y = a + bX (Y = 85,968 - 0.466 X = 85,502 X). The regression coefficient value obtained is -0.466 proves that the increasing work family conflict of an employee will affect the decrease in psychological well being, because any increase or decrease in the work family conflict variable will cause an increase or decrease in the psychological well being variable. , and the magnitude of the effect of work family conflict on psychological wel being is 20.6%, while the rest is influenced by other variables not examined in this study.